2020
DOI: 10.1186/s12903-020-1051-7
|View full text |Cite
|
Sign up to set email alerts
|

Dental professionals’ experiences of managing children with carious lesions in their primary teeth – a qualitative study within the FiCTION randomised controlled trial

Abstract: Background The lack of evidence for the effective management of carious lesions in children’s primary teeth has caused uncertainty for the dental profession and patients. Possible approaches include conventional and biological management alongside best practice prevention, and best practice prevention alone. The FiCTION trial assessed the effectiveness of these options, and included a qualitative study exploring dental professionals’ (DPs) experiences of delivering the different treatment arms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…MAGIC was generally seen as an important study, but where clinical gatekeepers had successful practices using other pre-medications, or nonpharmacological techniques, stakeholders reported an unwillingness to engage with MAGIC. Using an unfamiliar approach, particularly when there are high stakes if it is not successful, can also be a challenge for stakeholders [13]. Again, this points to the potential benefits of engagement work by researchers involved in an RCT, as well as qualitative research as part of feasibility studies to understand opinions and concerns about an intervention [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAGIC was generally seen as an important study, but where clinical gatekeepers had successful practices using other pre-medications, or nonpharmacological techniques, stakeholders reported an unwillingness to engage with MAGIC. Using an unfamiliar approach, particularly when there are high stakes if it is not successful, can also be a challenge for stakeholders [13]. Again, this points to the potential benefits of engagement work by researchers involved in an RCT, as well as qualitative research as part of feasibility studies to understand opinions and concerns about an intervention [9].…”
Section: Discussionmentioning
confidence: 99%
“…As well as understanding why patients do and do not agree to participate in RCTs, recruitment needs to be considered from the perspective of stakeholders, such as clinicians, research nurses and those involved in designing the trial. Qualitative research on stakeholders' experiences highlights the challenges involved in operationalising the trial protocol into usual practice, fully understanding the intervention, and issues relating to professional roles [6,[11][12][13][14][15]. Barriers and enablers to recruitment relate to various factors, including those among patients, practitioners and within particular settings, as has been identified by French and Stavropoulou and Team and colleagues [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The trial found no evidence of a difference between arms in its primary outcome; dental pain and/or dental infection, nor were any differences detected in the trial's secondary outcomes of caries incidence, child oral health-related quality of life or dental anxiety between the three caries management strategies [5,6]. When acceptability of the management strategies was evaluated from the perspective of the DPs providing the treatment, they described their responsibility to select an appropriate strategy for each individual child, based on discussions with the child and parent and their own clinical experience [7]. Consequently, the trial recorded cross-arm deviations for 6% of the total visits.…”
Section: Discussionmentioning
confidence: 99%
“…The FiCTION trial included clinical, economic and patient-reported outcomes, which have been reported elsewhere [5,6]. The trial also aimed to explore the acceptability of the treatment strategies for the DPs delivering the treatment [7] the children receiving the treatment and their parents. There is growing recognition of the importance of evaluating the acceptability of health interventions, in addition to their effectiveness [8].…”
Section: Biological With Best Practice Prevention (B + P)mentioning
confidence: 99%
“… 19 There are few studies that have dealt with the lived experience of performing dental treatment, e.g. when dental professionals manage children with carious lesions 20 but no study has yet explored what it means to perform a periodontal treatment in the professional context of general dentistry.…”
Section: Introductionmentioning
confidence: 99%